Serum Exosomal Circular RNA Expression Profile and Regulative Role in Proliferative Diabetic Retinopathy - Li, Xinsheng; Wang, Jingfan; Qian, Huiming; Wu, Yan; Zhang, Zhengyu; Hu, Zizhong; Xie, Ping (Frontiers in Genetics, 2021)
Background Proliferative diabetic retinopathy (PDR), as one of the main microvascular complications of diabetes mellitus, seriously threatens the visual function of the working-age population; yet, the underlying pathogenesis is still poorly understood. This study aimed to identify the distinct exosomal circular RNA (circRNA) expression in PDR serum and preliminarily explore the potential pro-angiogenic mechanism of specific exosomal circRNAs. Methods We collected serum samples from 10 patients with PDR and 10 patients with age-matched senile cataract to detect the exosomal differentially expressed genes (DEGs) of circRNAs via high-throughput sequencing, followed by validation with quantitative real-time PCR (qRT-PCR). Next, bioinformatics analyses including competitive endogenous RNA (ceRNA) network, protein–protein interaction network (PPI), and functional enrichment analyses were performed. In addition, the potential function of circFndc3b (hsa_circ_0006156) derived from high-glucose-induced endothelial cells was analyzed in human retinal vascular endothelial cells (HRVECs). Results In total, 26 circRNAs, 106 microRNAs (miRNAs), and 2,264 messenger RNAs (mRNAs) were identified as differentially expressed in PDR serum exosomes compared with cataract serum exosomes (fold change > 1, P < 0.05). A circRNA–miRNA–mRNA ceRNA network was established. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that the mRNAs were mainly enriched in the PI3K–Akt signaling pathway, MAPK signaling pathway, Wnt signaling pathway, and VEGF signaling pathway. The PPI network and module analysis identified 10 hub genes, including RhoA, Cdc42, and RASA1. Finally, circFndc3b and exosomes derived from high-glucose-induced endothelial cells were identified with the capability to facilitate angiogenesis in vitro. Conclusion Aberrant profiling of exosomal circRNAs in PDR serum was identified. CircFndc3b derived from high-glucose-induced endothelial cells may play an important role in the angiogenesis of PDR.